2017
DOI: 10.1088/1361-6463/aa8e75
|View full text |Cite
|
Sign up to set email alerts
|

Effect of double-pulse-laser polarization and time delay on laser-assisted etching of fused silica

Abstract: High-aspect-ratio microchannels were fabricated by femtosecond-double-pulse-laser-assisted polarization-selective etching. The etching rate and uniformity of the microchannels were mainly determined by the double-pulse polarization and time delay. We found that when the two sub-pulses had a different polarization (one linear, the other circular), the microchannel etching rate increased by a factor of 10 compared to when both sub-pulses were linearly polarized. The maximum etching rate was obtained when the pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Femtosecond (fs) laser with ultrashort pulse durations and high peak power without causing thermal damage to the part is usually employed in nanostructures manufacture and nanomaterials modification [24,25,26,27]. It is an ideal tool for the excitation of surface plasmon resonances (SPRs), because the fs laser excitation can minimize thermal damage in the adjacent nanomaterials and substrate materials [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Femtosecond (fs) laser with ultrashort pulse durations and high peak power without causing thermal damage to the part is usually employed in nanostructures manufacture and nanomaterials modification [24,25,26,27]. It is an ideal tool for the excitation of surface plasmon resonances (SPRs), because the fs laser excitation can minimize thermal damage in the adjacent nanomaterials and substrate materials [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…This has mainly been attributed to a reduction of nonlinear ionization due to the intensity decrease when splitting the pulse in two, as well as to a screening effect from the plasma [17][18][19][20][21]. In contrast, the case of in-volume material excitation, at fluences lower than the ablation threshold, shows stronger modifications of fused silica (index of refraction, nanogratings formation) with double pulses in comparison with single pulses of identical total energy, for inter-pulse delay typically on the order of 10-100 ps [22][23][24][25][26][27]. The stronger modifications were attributed to an increase of the total deposited energy because of a higher absorption of the second pulse by the material softened after the first pulse.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the theoretical and experimental research has focused on laser-induced periodic surface structures upon an fs doublepulse sequence irradiation in the time domain from sub-ps to dozens of ps. Related applications include the enhancement of etching, ablation, micro welding [29][30][31], and control of electron dynamics [32]. For example, Shimotsuma et al observed ultrafast writing dynamics of formed nanograting in fused silica within 10 ps, and successfully demonstrated rewritable 5D optical memory and polarization imaging filter mediated by birefringence intensity [28,33].…”
Section: Introductionmentioning
confidence: 99%